Intervensi Pembersihan Lendir pada Pasien Gagal Pernapasan dengan Ventilator: Sebuah Narratif Review - Etika Emaliyawati; Aan Nuraeni; Ristina Mirwanti; Firman Sugiharto; Diana Kusuma Astuti; Evania Altsa Radinka; Siti Nur Damayanti (Universitas Malahayati Lampung, 2023)
ABSTRACT Acute respiratory failure (ARF) is a disorder of the pump function of the respiratory muscles or dysfunction of the lungs. Patients with respiratory failure use mechanical ventilation for breathing apparatus. However, mechanical ventilation often interferes with airway clearance and coughing. So intervention is needed to remove mucus from the airways. This study aimed to identify interventions that can be performed to reduce and clear mucus in patients with respiratory failure who are attached to a mechanical ventilator. This study used the narrative review method with the keywords “patient with ventilator OR patient with mechanical ventilation OR mechanically ventilated patient OR patient undergoing mechanical ventilation” AND “intervention OR strategies OR best practice OR treatment OR therapy OR program OR management” AND “mucus clearance OR airway clearance OR sputum clearance”. The databases used include Scopus, PubMed, EBSCO, Oxford. The results of 5 articles were obtained which consisted of various effective interventions for removing secretions such as ventilator hyperinflation mode, head down tilt position, manual chest compression (MCC), mechanical insufflation-exsufflation (MI-E), and chest physiotherapy. This intervention is effective in expelling mucus, increases expiratory flow bias which has the potential to increase secretions removal maneuvers, facilitates mucus cleaning during suctioning, and increases aeration in the dorsal lung without affecting blood gas analysis results. These various interventions can be a choice of solutions to help problems that arise due to the use of mechanical ventilation. Keywords: Acute Respiratory Failure, Mucus Suction, Ventilator ABSTRAK Gagal napas akut (GGA) merupakan gangguan fungsi pompa otot pernapasan atau disfungsi pada paru-paru. Penderita gagal napas menggunakan ventilasi mekanik untuk alat bantu napas. Namun, ventilasi mekanis sering mengalami gangguan pembersihan lendir saluran napas dan batuk. Sehingga diperlukan intervensi untuk mengeluarkan lendir dari saluran napas. Penelitian ini bertujuan untuk mengidentifikasi intervensi-intervensi yang dapat dilakukan dalam menurunkan dan membersihkan lendir pada pasien dengan gagal napas yang terpasang ventilator mekanik. Penelitian ini menggunakan metode narrative review dengan kata kunci “patient with ventilator OR patient with mechanical ventilation OR mechanically ventilated patient OR patient undergoing mechanical ventilation” AND “intervention OR strategies OR best practice OR treatment OR therapy OR program OR management” AND “mucus clearance OR airway clearance OR sputum clearance”. Database yang digunakan antara lain scopus, pubmed, EBSCO, oxford. Didapatkan hasil 5 artikel yang terdiri dari berbagai intervensi yang efektif untuk mengeluarkan sekret seperti mode hiperinflasi ventilator, posisi head down tilt, manual chest compression (MCC), mechanical insufflation-exsufflation (MI-E), dan fisioterapi dada. Intervensi ini efektif dalam pengeluaran mukus, meningkatkan aliran ekspirasi bias yang berpotensi meningkatkan manuver pengeluaran sekret, mempermudah pembersihan mukus ketika suction, dan meningkatkan aerasi di bagian dorsal paru tanpa mempengaruhi hasil analisa gas darah. Berbagai intervensi ini dapat menjadi pilihan solusi untuk membantu permasalahan yang ada akibat penggunaan ventilasi mekanik. Kata Kunci: Gagal Napas Akut, Penghisapan Lendir, Ventilator